2019
DOI: 10.1002/cctc.201801990
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine Ruthenium Oxide Nanoparticles Supported on Molybdenum Oxide Nanosheets as Highly Efficient Electrocatalyst for Hydrogen Evolution in Acidic Medium

Abstract: Engineering of efficient, robust and inexpensive Pt-free catalysts for the hydrogen evolution reaction has drawn great attention, and there is a rapidly growing demand for electrochemical water-splitting reactions. Here, we report, for the first time, synthesis of ruthenium oxide nanoparticles supported on molybdenum oxide nanosheets (MoO 3 @RuO 2 ). This composite catalyst was prepared sonochemically, followed by calcination of the product in air at 400°C for one hour. The as-synthesized MoO 3 @RuO 2 composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…The HER activity of MoO3/MoS2 remained stable even if it was tested for 10,000 cycles ( Figure 3c) [56]. Besides, Pt [59], Pd [60], RuO2 [19] can also load on MoO3, to get excellent electrocatalysts for electrocatalytic hydrogen evolution. [49].…”
Section: Electrocatalytic Hydrogen Evolution Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The HER activity of MoO3/MoS2 remained stable even if it was tested for 10,000 cycles ( Figure 3c) [56]. Besides, Pt [59], Pd [60], RuO2 [19] can also load on MoO3, to get excellent electrocatalysts for electrocatalytic hydrogen evolution. [49].…”
Section: Electrocatalytic Hydrogen Evolution Reactionsmentioning
confidence: 99%
“…Stability is another crucial factor for catalysts. In general, MoO 3 -based nanocatalysts, which served as substrate or active center, possessed excellent stability in both acid and alkaline media for HER [19,55]. The current density can remain stable at a specific voltage for 12 [55], 24 [19], and even 40 h [65].…”
Section: Electrocatalytic Hydrogen Evolution Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports suggest that metal NPs synthesized via the sol-gel technique are more active than those synthesized through the adsorption-reduction technique, as the former is capable of generating nanocatalysts of suitable particle size with high surface activity. 33 As depicted in Scheme 3, the structures can broadly be classied as monometallic or bimetallic NPs. Monometallic NPs can further be subdivided into catalytic and bioactive NMs, based on the presence or absence of substrate adsorption.…”
Section: Classification Based On Synthetic Protocolmentioning
confidence: 99%
“…Previous researches have revealed that charge transfer at the interfaces of hybrid plays a significant role in the catalytic enhancement for HER. [108][109][110] For instance, highly dispersed β-Mo 2 C nanoparticles with an average size of 5 nm embedded in ordered mesoporous carbon (OMC) composite has been synthesized via the pyrolysis of Mo salts and OMC precursors. [111] Figure 6a,b shows the highly ordered parallel mesoporous carbon channels with well-dispersed Mo 2 C nanoparticles loading.…”
Section: Heterostructurementioning
confidence: 99%